Barriers to and facilitators for involving clinical staff members in managing patients with musculoskeletal disorders in general practice: a systematic review - Riis, Allan; Hofmann Merrild, Camilla; Nielsen, Josephine; Afzali, Tamana; Skovdal Rathleff, Michael; Elgaard Jensen, Cathrine; Laust Thomsen, Janus (UCN Perspektiv, 2023)
In Denmark, musculoskeletal (MSK) pain is the most common reason for consultations in general practice. Despite the high frequency of MSK consultations, patients do not always receive guideline concordant support to self-manage their condition and advice to stay physically active. Clinical staff might be able to assist with this. The aim of this project is to describe the barriers to and the facilitators for involving clinical staff in MSK management in general practice through a systematic review. We found that although hysiotherapists possess the necessary skills to deal with MSK pain, they lack the competencies to handle patients with multimorbidity and patients without MSK-related conditions in order to obtain a holistic approach of patients in general practice. Also, nurses need training, especially in delivering basic MSK counselling, which includes advising patients to stay active as well as avoid bedrest and pain killers as stand-alone treatment strategies. Therefore, we conclude that involving physiotherapists and nurses in MSK pain management is believed to increase the quality of MSK care, while the lack of skills to take a holistic view is a perceived barrier. More studies are needed to inform educational programmes for physiotherapists and nurses to manage MSK disorders in general practice.